Utility of the REM sleep behavior disorder screening questionnaire (RBDSQ) in Parkinson’s disease patients - Nomura, Takashi; Inoue, Yuichi; Kagimura, Tatsuo; Uemura, Yusuke; Nakashima, Kenji (Sleep medicine, 2011)
We evaluated the usefulness of the REM sleep behavior disorder (RBD) screening questionnaire (RBDSQ) among patients with Parkinson’s disease (PD). Forty-five patients with PD were evaluated (22 male and 23 female, 72.9 ± 9.1 years old). After patients completed the RBDSQ, we conducted interviews regarding RBD symptoms and performed polysomnographic examinations on the subjects. We then compared RBDSQ scores among the following groups: PD with RBD ( n = 19), PD without RBD ( n = 26), and idiopathic RBD ( n = 31, 22 male and 9 female, 67.8 ± 6.5 years old), and estimated the cut-off score for an RBD diagnosis. RBDSQ scores in PD with RBD and idiopathic RBD groups were similar and higher than those in the PD without RBD group (PD with RBD: 7.2 ± 1.9, idiopathic RBD: 7.9 ± 2.8, PD without RBD: 2.9 ± 1.6). Cronbach’s α for RBDSQ sub-scores was 0.73, suggesting a fair internal consistency. A receiver-operator characteristics curve revealed that a total score of 6 points on the RBDSQ represented the best cut-off value for detecting RBD (sensitivity = 0.842, specificity = 0.962). RBDSQ could be a useful tool for the screening of RBD in PD patients.